Cross-sectional survey exploring current intake practices for dogs admitted to animal shelters in Texas: a descriptive study - Cranford, Mackenzie; Bing, Abbey; Cisneros, Alissa; Carroll, Amber D.; Porter, Hannah; Stellato, Anastasia Chiara (Frontiers in Veterinary Science, 2023)
Entering an animal shelter is a stressful experience for dogs that can impair their welfare, adoptability, and shelter staff safety; thus, it is crucial to reduce the stress experienced during intake. This study investigated the current intake practices for dogs admitted in animal shelters in Texas, USA. To gather data, an online survey was designed and distributed to shelter employees responsible for intake at animal shelters. The survey collected information about examination procedures, the type of information collected from owner-surrenders, as well as the housing environment for the dogs. Survey participants (n=64) were shelter staff from municipal (59%, 38/64) and private shelters (23%, 15/64) in 47 counties. Handling techniques reported to be used during intake exams varied depending on the dog's behavior, with participants reporting higher restraint for aggressive dogs and lower restraint for calm dogs. If the dog was displaying fear, participants reported offering food and attention (89%, 47/53), using towel restraint (64%, 34/53) and conducting the exam on someone's lap (49%, 26/53). In cases of aggression, it was commonly reported to use muzzles (81%, 42/52) and catch poles (77%, 40/52), and shorten the exam (71%, 37/52). After the exam, most reported placing dogs on the adoption floor (45%, 27/60) or placing them wherever space was available (20%, 12/60). Results provide descriptive information on current intake procedures and routine handling techniques used in Texas shelters.Future research should explore shelter dog responses to routine handling techniques to support the development of evidence-based protocols during routine intake examinations and procedures.